PROYEKSI PERTUMBUHAN PENDUDUK KABUPATEN PEGUNUNGAN ARFAK MENGGUNAKAN MODEL LOGISTIK - Kukuh Silvia Dwi Anggraeni; Tri Widjajanti Widjajanti; Rium Hilum Rium Hilum (Jurnal Natural, 2022)
Arfak Mountains Regency is an expansion area of Manokwari Regency which was formed based on the law of the Republic of Indonesia Number 24 of 2012 concerning the expansion of Arfak Mountain Regency in West Papua Province. The population growth of the Arfak Mountains Regency which has increased after the expansion can cause social problem in the area. social problems arising from the increase in population can be anticipated by using population growth projection. The purpose of this paper is to determine the logistic model and project population growth in the Arfak Mountains Regency. The results of this study are the mathematical model of population growth in the Arfak Mountains Regency using the logistic model is: The projected population growth of Arfak Mountains Regency in 2030 is people with an intrinsic growth rate of which is .